Comparative Studies on The Efficacy of Some Fungicides Activities on Fungal Seed Borne Pathogens of Commercial Maize Seeds - Jane, Egbo Nwakaku; Chukwudi, Ugoh Sylvester; Sunday, Olisa Babafemi (Food, Agriculture and Natural Resources - NETWORKS, 2024)
This study investigated the efficacy of some fungicides activities on fungal seed borne pathogens of two commercial maize seeds (Sammaz 15 and Sammaz 52). A total of 2500 seeds were randomly picked for each variety to represent a working sample from the seed reference collections. Out of the 2500 seeds, 400 seeds were surface–sterilized with 10% sodium hypochlorite solution, cultured and examined microscopically for the presence of fungal pathogens. Molecular analysis confirmed that all isolated pathogens matched with the reference accession from NCBI molecular database. Seeds were treated with different dosages of fungicides viz Thiram and Metalaxy + Tebuconazole and incubated for 5 days. The effect of the various fungicides on the incidence of seed- borne fungi, effect on seed germination and interaction of the fungicide were evaluated and analyzed. Percentage occurrence of the fungal pathogens revealed that Sammaz 15 have F. solani (29.0%), A. flavus (20.3%), A. niger (19.0%) and Rhizpus stolanifera (15.0%). In Sammaz 52, A.niger (40.0%), A. flavus (19.7%) and F. solani (27.0%). It was observed that F. solani was predominant in sammaz 15 while A. niger was predominant in Sammaz 52. Thiram (45.88 mm) at all doses showed greater inhibitory effects on mycelia growth than Metalaxyl + Tebucanozole (24.25 mm). The correlation analysis performed on the data set reveals that there is a negative significant correlation between zone of inhibition and percent disease incidence (r = -0.99***), but the relationship was positive with number of non-infected seeds (r = 0.99***). This shows that increasing the zone of inhibition will increase the number of non-infected seeds and the normal seedling (germination percentage). Thiram fungicides observed to be more effective in reducing the disease incidence than Metalaxyl fungicides.